Bundle approach in sepsis management - An overview - Vinayak Patki; Sachin Jangam; Jennifer Antin (Wolters Kluwer Medknow Publications, 2018)
The journey of sepsis management has evolved over last two decades with background of continuous evidenced based guidelines and their timely updation through serving sepsis campaign (SSC). Every update in the SSC guideline has made significant positive impact over sepsis related morbidity and mortality.Care bundles are a group of best evidence- based interventions which when instituted together,gives maximum outcome benefit. These are simple, uniform and have universal practical applicability.Sepsis bundles represent key elements of care regarding the diagnosis and treatment of patients with septic shock. These bundles allows to convert complex guidelines into meaningful changes in behaviour. The most recent bundle update bundle requires quick action to rescue patients and when necessary escalate care rapidly to reduce mortality and morbidity. But recommendations from these bundles/guidelines cannot replace the clinician's decision-making capability who is monitoring the dynamic changes in clinical variable of patient at bedside.